Coordinating Public Debt and Monetary Management During Financial Reforms - Leite, Sergio (Washington, D.C. : International Monetary Fund, 1992)
The paper analyzes the interplay between public debt and monetary management during financial reforms, and provides suggestions on collaboration between the central bank and the treasury to achieve common objectives. It discusses monetary policy and public debt at the onset and through different phases of a financial reform and emphasizes that many objectives of public debt and monetary management are mutually supportive. It recommends the setting up of units to deal with public debt issues both at the treasury and the central bank, as well as a committee to coordinate public debt and monetary management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet